Opredelenie individual'nykh biomekhanicheskikh kharakteristik tekhniki pryzhkov v vodu - Tikhonov, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this paper was to increase the training efficiency of Russian diving team for XXVIII Olympic games. The task was to develop the way of definition of diving technique individual biomechanical features. There was used the method of videogramme processing developed by the author of this paper. There the frame-by-frame measurement of angular movings of an athlete with account of his body's weights geometry and rules of the mechanics in it's basis was put. The following periods of rotating jumps structure are allocated: pushing away, transition in the given pose, rotating, disclosing and entrance in a water. The way of videogramme processing allows to receive the following biomechanical parameters: the time, amplitude, angular speeds of the athlete's body moving. The using of these biomechanical parameters in training process raises efficiency of athlete's technical training.